The notion and basic principles of restorative justice - Ćopić Sanja (Temida, 2007)
One of the most important achievements of the contemporary criminal justice system and criminal policy is development of the concept of restorative justice. Contemporary concept of restorative justice was developed in 1970s on the basis of the criticism of the traditional criminal law and criminal justice system. Since that time, it has been developing through different programs in many countries. Reform of the criminal justice system in Serbia staring from 2002 went into direction of entering elements of restorative justice into existing criminal justice system. In that sense, development of restorative justice is still at the beginning in our country. However, it can be noticed that there is a low level of awareness on the nature and importance of restorative forms of response to crime among our professionals, as well as a lack of understanding of the concept itself. Due to that, the aim of the paper is to enable better understanding of restorative concept in general through defining restorative justice and basic principles it relies on. That may put a basis for further recognition of restorative elements in our criminal justice system, which may provide adequate implementation of relevant provisions of restorative character in practice. .